Calitatea vieții studenților. Studiu de caz: Mulțumirea studenților din trei universități clujene față de aspecte legate de calitatea vieții - George Florin VLAS (Revista Transilvană de Ştiinţe Administrative, 2015)
Considering that the profle of the city of Cluj-Napoca is a „university” one, I analyzed the qua-lity of life of students from Cluj-Napoca based on their level of satisfaction towards general aspects of quality of life, the activity of teaching and lear-ning, the materials and equipment provided by the faculty, and the services and facilities offered by the university. Surprisingly, I found out that there does not exist a quality of life model of analysis for this segment of population, for which I elaborated a model based on the means attained by each of the aspects previously mentioned.The research part includes the quantitative analysis of the data collected from the application of a questionnaire on the students of three univer-sities from Cluj-Napoca: Babeș-Bolyai University, University of Agricultural Sciences and Veterinary Medicine, and Technical University of Cluj-Napoca.The analysis is focused on four major objecti-ves: (1) calculation and interpretation of the means attained by each of the four dimensions of the qu-estionnaire (satisfaction towards general aspects of quality of life, the activity of teaching and learning, the materials and equipment provided by the faculty, and the services and facilities offered by the univer-sity); (2) analysis of frequencies of each question from the questionnaire; (3) testing and interpreting the hypotheses of the study; (4) elaboration of a model of analysis of students’ quality of life.